Association of genetic variants and expression levels of porcine FABP4 and FABP5 genes. (27th October 2017) - Ballester, M.; Puig‐Oliveras, A.; Castelló, A.; Revilla, M.; Fernández, A. I.; Folch, J. M.
Summary: The FABP4 and FABP5 genes, coding for fatty acid transport proteins, have long been studied as positional candidate genes for SSC4 QTL affecting fat deposition and composition traits in pigs. Polymorphisms in these genes, FABP4 :g.2634_2635insC and FABP5 :g.3000T>G, have previously been associated with fatness traits in an Iberian by Landrace cross (IBMAP). The aim of the present work was to evaluate the functional implication of these genetic variants. For this purpose, FABP4 and FABP5 mRNA expression levels in 114 BC1_LD animals (25% Iberian × 75% Landrace) were analyzed using real‐time quantitative PCR in backfat and muscle. FABP4 gene expression in backfat, but not in muscle, was associated with FABP4 :g.2634_2635insC. In contrast, FABP5 :g.3000T>G was not associated with gene expression levels. An expression‐based genome‐wide association study highlighted the FABP4 :g.2634_2635insC polymorphism as the polymorphism most associated with FABP4 gene expression in backfat. Furthermore, other genomic regions associated in trans with the mRNA expression of FABP4 in backfat and FABP5 in muscle were also identified. Finally, two putative transcription binding sites for PPARG and NR4A2 may be affected by the FABP4 :g.2634_2635insC polymorphism, modifying FABP4 gene expression. Our results reinforce FABP4 as a candidate gene for fatness traits on SSC4.